Peran Guru dalam Membangun Minat Menghafal Al-Qur'an Siswa di SD Tahfidzul Qur'an Ad Diin Kuwarasan - Dewi Rofikotun Nisa; Mustajab Mustajab (IAINU Kebumen, 2023)
This study aims to describe the role of teachers in building interest in memorizing the Qur'an students in SD Tahfidzul Qur'an Ad Diin Kuwarasan. Penelitin method uses a qualitative approach. In the data collection is done by observation techniques, interviews, documentation, and questionnaires. Data analysis techniques through data reduction, data presentation, and conclusions. The results showed that the role of teachers in building interest in memorizing the Qur'an is to provide motivation, use methods that match the students, and work with parents. Students ' interest in memorizing the Qur'an is seen from the enthusiasm in tahfidz activities, repeating (murojaah) before advancing to be deposited and the increase in memorization deposited to the teacher because of motivation. Factors supporting teachers in the implementation of tahfidz learning include learning media, provide motivation to students, assistance from friends Cottage, facilities and infrastructure, cooperation with parents. Factors inhibiting teachers in the implementation of learning tahfidz namely students who memorize the Qur'an at home in, there are students who memorize with a quiet atmosphere is not noisy, lazy nature of the students, students who do not focus in memorizing the Qur'an.